2021
DOI: 10.3390/ijms22168911
|View full text |Cite
|
Sign up to set email alerts
|

HOXB8 Counteracts MAPK/ERK Oncogenic Signaling in a Chicken Embryo Model of Neoplasia

Abstract: HOX transcription factors are members of an evolutionarily conserved family of proteins required for the establishment of the anteroposterior body axis during bilaterian development. Although they are often deregulated in cancers, the molecular mechanisms by which they act as oncogenes or tumor suppressor genes are only partially understood. Since the MAPK/ERK signaling pathway is deregulated in most cancers, we aimed at apprehending if and how the Hox proteins interact with ERK oncogenicity. Using an in vivo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Cleaved caspase-3 (CASP3) immunofluorescence showed that MEK1ca expression also leads to an increase of cell death on the electroporated side ( Fig. 3 , see also quantification one day post-electroporation in [72] ). This increase of apoptosis is consistent with previous studies showing that ERK oncogenic activity, in addition to its well-described hyperproliferative effects, also promotes apoptosis, autophagy and senescence [9] .…”
Section: Resultsmentioning
confidence: 92%
“…Cleaved caspase-3 (CASP3) immunofluorescence showed that MEK1ca expression also leads to an increase of cell death on the electroporated side ( Fig. 3 , see also quantification one day post-electroporation in [72] ). This increase of apoptosis is consistent with previous studies showing that ERK oncogenic activity, in addition to its well-described hyperproliferative effects, also promotes apoptosis, autophagy and senescence [9] .…”
Section: Resultsmentioning
confidence: 92%
“…The serological testing and immunoblot assay by M Volkmann et al revealed humoral immune response to p53 exclusively in HCC patients and the presence of p53 antibodies in HCC patients was not dependent on alpha-fetoprotein level [ 35 ]. The mitogen-activated protein kinase (MAPK) signaling pathways played essential roles in diverse biological events including survival, dissemination, and resistance to drug therapy of human tumor cells [ 38 – 40 ]. Wang et al reported activation of MAPK signaling pathway during the promotion of HCC development stimulated by linc00601 upregulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%